Foundations and Objectives of Environmental Education in the works of Ayatollah Javadi - mohammad davoodi; fatemeh vojdany (اخلاق وحیانی, 2017)
Environmental issues threaten the lives of modern societies, and the environmental education can be a way out of this threatened lives. Environmental education is a process that develops knowledge, attitudes, and actions needed for treating the environmental issues. The aim of the present study is to find out the foundations and objectives of environmental education according to Ayatollah Javadi’s Views. The methodology of this research is descriptive and inferential. Apart from determining the general foundation and objective of environmental education, i.e. instructing students to be good believer men/women, six meddle objectives have been derived from Ayatollah Javadi’s works, which are: educating the monotheistic attitude towards world and environment, making the student familiar with the philosophy of creation and his/her relationship with the environment, making the student aware of his/her responsibilities for the environment, developing the sense of friendship with environment and religious responsibility for it, developing the sense of empathy with and obligation to the members of society and future generations, and training the necessary skills in developing the environment and the correct use of it. At the end, the instances of these objectives are examined in more details.